Rapid nongenomic effects of aldosterone in mineralocorticoid-receptor-knockout mice - Rossol-Haseroth, Karin; Gerdes, Dirk; Berger, Stefan; Feuring, Martin; Günther, Andreas; Herbst, Christel; Christ, Michael; Wehling, Martin (Biochemical and biophysical research communications, 1999)
In addition to genomic effects of aldosterone, rapid nongenomic effects of steroids have been reported in various tissues that were clearly incompatible with a genomic action of aldosterone. Rapid effects of aldosterone involve second messengers such as calcium and cAMP. Specific high affinity binding sites for aldosterone have been characterized in membranes for different cells, which probably transmit those rapid steroid effects. To date, it is unclear if these binding sites are modified classical mineralocorticoid receptors (MR) or if they represent an unrelated receptor protein. The aim of the present study was to investigate whether rapid aldosterone action still occurs in the absence of the classical MR. For this purpose we used the model of MR knockout mice. Rapid effects were analyzed in skin cells, measuring intracellular calcium and cAMP levels after stimulation with aldosterone. We found that rapid effects are not only present in MR knockout mice, but that the effects are even larger than in wild-type mice cells. The results of the present study demonstrate that the classic MR is dispensable for rapid aldosterone action. The study, thus, proves that a receptor different from the classic intracellular receptor is involved in rapid aldosterone signaling.
Online veröffentlicht am 25 Mai 2002
Gesehen am 19.10.2022